Tendências dos estudos de assembleias de epífitas vasculares na Floresta Atlântica: Uma revisão sistemática - Moreira, Vinicius José Silva Barbosa (2023)
The knowledge of the world's biomes, biodiversity, and their conservation status is a growing concern for researchers. However, problems such as lack of data and collections create knowledge gaps, such as the large number of undescribed species, a lack of knowledge about the geographic distribution of species, and a lack of knowledge about species' adaptations and tolerances to adverse conditions. Our aim was to conduct a quantitative review of vascular epiphyte inventories in the Atlantic Forest. To perform this work, we collected studies (articles, theses, dissertations, and conference abstracts) of vascular epiphyte assemblages from Web of Science, Scopus, Scielo, and Google Scholar databases. Our article search range was determined by the results from the terms "Vascular epiphytes" and "Atlantic Forest" in three languages: Portuguese, English, and Spanish. This primary search resulted in 471 studies. After manual filtering, in which only studies on vascular epiphyte assemblages in the Atlantic Forest were selected, we reached a total of 146 studies. Most of these studies used qualitative methodology and were published in Brazilian journals and in Portuguese. Conducting studies in sub-sampled regions of the Atlantic Forest and improving the sampling of less studied groups is important to reduce knowledge gaps in that biome, as well as to increase and improve sampling data that these studies provide. We concluded that the sampling of epiphytes in the Atlantic Forest is still poorly distributed, leaving many areas under-sampled. Overall, the information collected by these works lacks certain elements; therefore, future studies improving the quality and quantity of information collected on epiphytes in the Atlantic Forest are necessary to produce a more solid database on the entire extension of the phytogeographic domain.